Derivation of CaO-SiO2-Al2O3 system Slag Viscosity Equation by GP (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The knowledge of slag viscosity is essential in the field of the high-temperature metallurgical processes such as the kinetics of reactions and transport phenomena in metal-slag systems. It is a little difficult to exactly calculate the slag viscosity because of its strong nonlinear relation with its composition and temperature. In this paper, genetic programming (GP) was employed to derive CaO-SiO2-Al2O3 slag viscosity equation and to set its algorithm. By applying GP, it was automatically described as form of simple algebraic equation with composition (or basicity and content of Al2O3) and temperature. The average of relative errors between the calculated values and experimental data used for viscosity equation derivation was extremely low, as 17.1%. Computer simulations were made to evaluate the accuracy of derived viscosity equation, which were compared with many experimental viscosities and calculated results of other researchers, and the results proved that viscosity equation was relatively exact. Slag compositions and temperatures for simulation calculations were many experimental data which were not used in derivation of viscosity equation. The viscosities of CaO-SiO2-Al2O3 system slag can be simply and expediently predicted in a wide range of compositions and temperatures by using the derived viscosity equation.